Pengaruh Limbah Cair Pabrik Kelapa Sawit terhadap Pertumbuhan Bibit Mucuna bracteata - Fernando B. Manik; Seno Aji; Suratni Afriyanti; Nur Ariyani Agustina; Julaili Irni; Bayu Pratomo (Seminar Nasional Lahan Suboptimal, 2020)
Manik FB, Aji S, Afriyanti S, Agustina NA, Irni J, Pratomo B.  2020. The effect of application palm oil mill effluent on the growth mucuna bracteata seedlings. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimalke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Mucuna bracteata is a legum crop cover that has a high nitrogen fixation ability. This research aims to determined the effect of application and dosage levels Palm Oil Mill Effluent (POME) on the growth of Mucuna bracteata seedlings.This research was carried out in Jl. Agenda, Sei Putih Barat Subdstrict, Medan District from March to May 2020 using experimental method with non-factorial Randomized Complete Block Design (RCBD) with three replications and seven levels of POME treatment: (L0) Control/do not use POME, (L1) 25 ml/l solution, (L2) 50 ml/l solution, (L3) 75 ml/l solution, (L4) 100 ml/l solution, (L5) 125 ml/l solution, (L6) 150 ml/l solution. The research data were analyzed using analysis of variance and a further test Tuckey using software SAS version 9.1.3 at 5% level. The result of research indicates that application POME on the growth of Mucuna bracteata seedlings significantly effect on canopy fresh trendiland shoot dry weight. While on the root fresh weight, root dry weight, root shoot ratio, number of root nodules, and life percentage not significantly effect. The conclusion of this research is application POME (L6) 150 ml/l solution is the treatment that give the highest on shoot fresh weight 9,69 g, shoot dry weight 1,88 g, and number of  root nodules 20,58.